2014
DOI: 10.9790/3008-09131117
|View full text |Cite
|
Sign up to set email alerts
|

Antiplasmodial Effect of a Crude Extract of the Leaves of Xylopia Parviflora (Benth) On Plasmodium Yoelli Infection in Mice Fed Supplemented Dietary Pellets

Abstract: Abstract:The antiplasmodial activity of the leaves of Xylopia parviflora (Benth, L, FAM: Annonaceae)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
0
0
Order By: Relevance
“…Siwach et al (2013) concluded that various ex-situ and in-situ conservation practices need to be increased to battle the existing challenges. In India, many of medicinal plants are under threat because of excessive and unsustainable collection, utilization, over exploitation, or unskilled harvesting practices (Kumari et al, 2011) Many of the medicinal plants are profusely indigenous to developing countries (Bukar et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Siwach et al (2013) concluded that various ex-situ and in-situ conservation practices need to be increased to battle the existing challenges. In India, many of medicinal plants are under threat because of excessive and unsustainable collection, utilization, over exploitation, or unskilled harvesting practices (Kumari et al, 2011) Many of the medicinal plants are profusely indigenous to developing countries (Bukar et al, 2016).…”
Section: Introductionmentioning
confidence: 99%